Design, synthesis and biological evaluation of bivalent benzoxazolone and benzothiazolone ligands as potential anti-inflammatory/analgesic agents. Issue 13 (1st July 2015) - Abdelazeem, Ahmed H.; Khan, Shabana I.; White, Stephen W.; Sufka, Kenneth J.; McCurdy, Christopher R.
Graphical abstract: Abstract: Benzoxazolone and benzothiazolone were used as template blocks to develop two series of dimers as anti-inflammatory and analgesic agents based on the concept of bivalent ligands. The first series (I ) involved varying the carbon chain lengths extending from the piperazine core to the nitrogen atom of the dibenzo[ d ]oxazol-2(3 H )-one or dibenzo[ d ]thiazol-2(3 H )-one. The second series (II ) was designed by changing the attachment point. All compounds were screened for their in vitro anti-inflammatory activity in terms of the inhibition of inducible nitric oxide synthase (iNOS) and nuclear factor kappa B (NF-κB). Seventeen compounds inhibited both targets. Eleven of them exhibited IC50 values below 3 μM while five compounds showed IC50 values of 1 μM or below. Most of the compounds were found to be devoid of cytotoxicity against mammalian kidney and solid tumors cell lines up to 25 μg/mL. In vivo anti-inflammatory and antinociceptive studies revealed that compounds3j, 5t and8b have significant anti-inflammatory and analgesic activity comparable to that of indomethacin and ketorolac, respectively.